Virtual tactile feedback technology based on microcurrent stimulation: current status, challenges and future prospects - Xiong, Qiwei; Yao, Hongbo; Wang, Jiyu; Huang, Zhenghao; Luo, Junhong; Zhong, Changfu; Lin, Yihuan; Shu, Lin (Frontiers in Neuroscience, 2025)
With the rapid development of information technology, virtual reality (VR) technology and metaverse, which highlight personalized experience, have become hot spots in the development of information application industry. Visual, auditory, and tactile systems are the most common sensory systems used by human beings to perceive information about the external environment, facilitated by organs such as the eyes, ears, and skin, making it convenient and natural to interact with the outside world. The integration of virtual tactile feedback technology with audiovisual technology can further enhance the richness of interaction and achieve better immersion experience. Among the many tactile feedback technologies, electrical stimulation tactile feedback stands out due to its performance advantages such as device portability, high refresh frequency and precise control. However, electrical stimulation technology lacks a mature three-dimensional human tissue electrical stimulation conduction model with multipoint stimulation in theoretical research; the variety of virtual tactiles implemented in the research is limited, and there is a gap with real life; and there are fewer audio-visual tactile feedback fusion control models and equipment development problems. Based on these challenges, this paper combs through the latest research progress of microcurrent stimulation-based virtual tactile feedback technology in the field of human-computer interaction. “Microcurrent” here refers to the application of low-intensity electrical currents, specifically under 10 milliamperes, which provide precise and adjustable stimulation for enhancing tactile experiences in virtual and augmented reality applications. This summary outlining the technical characteristics and current research status of this research direction. Finally, the current problems and future development trends in this field are discussed in depth, and how to improve them in order to develop a broader application space is analyzed. By clarifying the potential value of tactile feedback in human-computer interaction, it is hoped to promote the future development of electrically stimulated tactile feedback technology in human-computer interaction, and to help develop a more natural, realistic, efficient and immersive human-computer interaction experience. This study uniquely integrates a systematic analysis of electrotactile perception mechanisms with emerging microcurrent stimulation technologies, providing practical guidelines and a novel reference framework for future research in virtual haptics.